FPGA Based Hardware Implementation For Green Cognitive Radio - Mohammad Shahnawaz Shaikh,; P. K. Khare, (Journal of Electronic Design Engineering, 2020)
Greening of communication systems leads to provide a solution for spectrum scarcity, high energy consumption, secure and fast transmission, and diversity for user access. OFDM with cognitive radio offer satisfactory solutions for all these heads. The cognitive radio system senses the surrounding environment possesses an electromagnetic spectrum. CR can adapt the radio parameter dynamically and autonomously. It improves the performance of the wireless communication system by endowing the opportunity to unlicensed secondary users temporarily. This arrangement maximizes network throughput with an interoperability facility. This paper presents a hardware implementation of a Green Cognitive Radio Communication (GCR) using an FPGA board. It defines the complete process of software and hardware implementation for the practical execution of this novel approach.